STRATEGI KEPALA SEKOLAH DALAM MENGATASI KEKURANGAN TENAGA PENDIDIK DI SMP ISLAM MA’ARIF SANGATTA UTARA - Yasin, Muhammad; Fadilah, Kiki (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
Strategy means careful planning of activities to achieve specific goals. The term strategy comes from the Greek strategy which is defined as "the art of the general" or the art of a commander which is usually used in warfare. This researcher uses a type of field research, where researchers directly research at the research site. By going directly to the research location, it is hoped that researchers can interact directly with related parties so that in conclusion, the results of this study are the principal's strategy for overcoming the shortage of educators at Ma'arif Sangatta North School. It has several steps including combining classes or multigrade, opening new job vacancies, carry out online learning. The inhibiting factors for school principals in overcoming this problem are inadequate school financing standards, incomplete facilities and infrastructure, and lack of teacher enthusiasm in the teaching and learning process at school. While the supporting factors are: many unemployed graduates, and optimizing the use of educational media and facilities.